Peran Kejaksaan dalam Mewujudkan Pemidanaan Humanis melalui Pidana Kerja Sosial Berdasarkan KUHP Baru - Sidik Dika prayoga (Jurnal Hukum Lex Generalis, 2026)
The introduction of community service punishment under Law Number 1 of 2023 concerning the Indonesian Criminal Code reflects a paradigm shift in sentencing from a retributive approach to a more humane and restorative one. This study aims to analyze the concept of humane sentencing through community service punishment and the role of the Attorney General’s Office of the Republic of Indonesia in its implementation. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that the implementation of community service punishment by public prosecutors has not been optimal, as it is a newly introduced form of punishment within Indonesia’s criminal justice system. The Attorney General’s Office plays a role in providing prosecutorial considerations, supervising the implementation of community service punishment and executing substitute sanctions when offenders fail to fulfill their obligations. Therefore, more detailed technical guidelines, enhanced prosecutorial capacity and stronger inter-agency coordination are required to support the effective implementation of community service punishment.